ENVIRONMENTAL FACTORS INFLUENCING RECREATION DURING CLIMATE CHANGE IN LVIV REGION IN RECENT YEARS - Snitynskyi В.; Lysak Г.; Mazurak О.; Panas Н.; Liubynets Н. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
Lviv region is facing environmental factors of climate change such as an increase in air temperature, a decrease in precipitation, snow cover, frequent cloudiness, and changes in topography. Roztochchia’s temperature monitoring over the past five years has shown an increase of 2.6°C, but some scientific publications report an increase of 3.2°C. This has led to a decline in the recreational sector and can have negative consequences for the socio-economic development of the region, which is rich in natural recreational resources. The change in temperature will affect plant cover, phytochromes, and recreational areas, leading to the disappearance of picturesque places. Skiing activities near the “Magic Lakes” in Yavoriv district may be affected due to the lack of long-laying snow cover. Ice skating is only possible on an artificial ice rink, while the ski slopes in Slavsk now require artificial snow cover. Natural water bodies are growing increasingly shallow and eutrophic, making them unsuitable for swimming. The management and increased consumer demand for the natural bowels of Skhidnytsia has caused violations of the recreation and sanitation conditions for visitors. A heavy downpour destroyed recreational facilities that did not comply with building requirements and used parts of the banks of the Skhidnychanka River for overhanging gazebos. The forestless mountain slopes did not manage to absorb rainwater, leading to flooding and other water-related problems. Although a decrease of precipitation by 110 mm per year is recorded in Lviv region, it is now of spontaneous nature. The use of water and balneological resources by vacationers requires them to be clean. Cloudy days have become more frequent in recent years, affecting the emotional perception of the recreation area. If it is raining and gloomy outside, sunbathing is impossible, reducing opportunities for leisure activities.